Safety and efficacy of Bacillus subtilisPB6 (Bacillus velezensisATCC PTA‐6737) as a feed additive for chickens for fattening, chickens reared for laying, minor poultry species (except for laying purposes), ornamental, sporting and game birds. (10th November 2020) - ; Bampidis, Vasileios; Azimonti, Giovanna; Bastos, Maria de Lourdes; Christensen, Henrik; Dusemund, Birgit; Kouba, Maryline; Fašmon Durjava, Mojca; López‐Alonso, Marta; López Puente, Secundino; Marcon, Francesca; Mayo, Baltasar; et al.
Abstract: Following a request from the European Commission, the Panel on Additives and Products or Substances used in Animal Feed (FEEDAP) was asked to deliver a scientific opinion on the renewal of the authorisation of Bacillus subtilis PB6, the extension of use to ornamental, sporting and game birds and a modification on the concentration of the said additive. The product under assessment is based on viable spores of a strain originally identified as Bacillus subtilis . During the course of the current assessment, the active agent has been redesignated as Bacillus velezensis ATCC PTA‐6737. The bacterial species B. velezensis is considered suitable for the qualified presumption of safety (QPS) approach to safety assessment. The identity of the active agent is established and the compliance with the other qualifications confirmed. Therefore, B. velezensis ATCC PTA‐6737 is presumed safe for the target species, consumers of products derived from animals fed the additive and the environment. The additive is not a dermal/eye irritant or a skin sensitiser. Exposure via inhalation is unlikely. In the previous assessments performed by the FEEDAP Panel, the additive showed to be efficacious as a zootechnical additive in feedingstuffs for chickens for fattening and chickens reared for laying at the level of 1 × 10 7 CFU/kg. Considering that efficacy at the same level has been shown, this conclusion is extrapolated to ornamental, sporting and gaming birds.